Efektivitas Prinsip Modifikasi Perilaku untuk Meningkatkan Kemampuan Menyikat Gigi Anak dengan Intelektual Disability Tingkat Sedang : Penelitian - Tri Wisda; Ade Rahmawati Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Self-care skills are fundamental abilities that support an individual’s independence in daily activities. Children with moderate intellectual disabilities often face challenges in performing self-care tasks, including toothbrushing, and therefore require structured guidance and training. This study aimed to examine the effectiveness of the total task chaining technique, supplemented with prompting, in improving toothbrushing skills in children with moderate intellectual disabilities. A single-subject research design with an A-B-A model was employed. The subject, MA, was an 8-year-old child with moderate intellectual disabilities who had limitations in self-care skills, particularly toothbrushing. The intervention was conducted over 14 sessions, guiding the subject to complete the entire sequence of toothbrushing steps in each session. Data were collected through observation of the toothbrushing behavior stages. The results indicated an improvement in toothbrushing skills following the intervention, with an N-gain score of 0.75, categorized as high. These findings suggest that the total task chaining technique, supplemented with prompting, is effective in enhancing toothbrushing skills in children with moderate intellectual disabilities, although ongoing parental guidance is recommended to ensure consistent behavior.